PSYCHOLOGICAL ISSUES OF DEPENDENCE OF NARCISSISM ON PERSONALITY TYPE - Alguliyev, Vusal (Health and Society, 2024)
The article examines the psychological issues of dependence on the personality type of narcissism. It was found that among the respondents with a negative self-concept, lack of empathy and envy of others’ achievements are more common. Here the sensitive side of narcissism is more evident. The influence of the dark side personality type and narcissistic personality traits on self-attitude factors is negative, except for a great sense of self-worth and belief in one’s own uniqueness. Research has shown that a great sense of self-worth and belief in one’s uniqueness are protective. It is a barrier not only to external threats, but also to innate ego threats. Research has shown that the relationship between self-attitude and narcissistic traits reflects the deep conflicts of the narcissistic personality between grandiosity and vulnerability, as well as the desire to protect opinions.